The independent prediction study of the effect of heart-type fatty acid binding protein on the severity and long-term cardiac function in Covid-19 patients - Yin, Li; Hailong Wang; Shao, Jiang; Mou, Huaming; Su, Li (Journal of the Pakistan Medical Association, 2023)
The study was conducted to assess the predictive ability of the heart-type fatty acid binding protein (HFABP) on the severity and long-term cardiac function of Covid-19 infected persons. In the case of negative HsTn-T, we determined whether HFABP was related to the severity of Covid-19 or it was the long-term impact of cardiac function. Chi-square test and t-test were used to evaluate whether HFABP level was an independent predictor of myocardial injury and whether it was related to the severity of Covid-19 and the long-term impact of cardiac function. Among the 20 patients in each of the two groups (mild and severe), 27.5% of all had elevated HFABP. Two were HFABP positive in the mild group, and nine were HFABP positive in the severe group, with a significant difference between the two groups (P=0.013). —Continue